IDNLearn.com offers a comprehensive solution for all your question and answer needs. Join our interactive Q&A platform to receive prompt and accurate responses from experienced professionals in various fields.
Sagot :
To solve the equation [tex]\(\frac{7y + 4}{y + 2} = \frac{-4}{3}\)[/tex], follow these step-by-step instructions:
1. Clear the Fraction:
To eliminate the fraction, cross-multiply the terms. This means multiplying both sides of the equation by the denominators:
[tex]\[ 3(7y + 4) = -4(y + 2) \][/tex]
2. Distribute the Terms:
Next, distribute the constants on both sides:
[tex]\[ 21y + 12 = -4y - 8 \][/tex]
3. Combine Like Terms:
Move all the [tex]\(y\)[/tex] terms to one side and the constant terms to the other side. You can do this by adding [tex]\(4y\)[/tex] to both sides and subtracting [tex]\(12\)[/tex] from both sides:
[tex]\[ 21y + 4y = -8 - 12 \][/tex]
Simplify the equation:
[tex]\[ 25y = -20 \][/tex]
4. Solve for [tex]\(y\)[/tex]:
Finally, divide both sides by 25 to isolate [tex]\(y\)[/tex]:
[tex]\[ y = \frac{-20}{25} \][/tex]
Simplify the fraction:
[tex]\[ y = -0.8 \][/tex]
So, the solution to the equation [tex]\(\frac{7y + 4}{y + 2} = \frac{-4}{3}\)[/tex] is [tex]\(y = -0.8\)[/tex].
1. Clear the Fraction:
To eliminate the fraction, cross-multiply the terms. This means multiplying both sides of the equation by the denominators:
[tex]\[ 3(7y + 4) = -4(y + 2) \][/tex]
2. Distribute the Terms:
Next, distribute the constants on both sides:
[tex]\[ 21y + 12 = -4y - 8 \][/tex]
3. Combine Like Terms:
Move all the [tex]\(y\)[/tex] terms to one side and the constant terms to the other side. You can do this by adding [tex]\(4y\)[/tex] to both sides and subtracting [tex]\(12\)[/tex] from both sides:
[tex]\[ 21y + 4y = -8 - 12 \][/tex]
Simplify the equation:
[tex]\[ 25y = -20 \][/tex]
4. Solve for [tex]\(y\)[/tex]:
Finally, divide both sides by 25 to isolate [tex]\(y\)[/tex]:
[tex]\[ y = \frac{-20}{25} \][/tex]
Simplify the fraction:
[tex]\[ y = -0.8 \][/tex]
So, the solution to the equation [tex]\(\frac{7y + 4}{y + 2} = \frac{-4}{3}\)[/tex] is [tex]\(y = -0.8\)[/tex].
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.